FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SECARA ONLINE (Studi Empiris pada Perusahaan Sektor Keuangan tahun 2020 di BEI) - Amelia Savitri; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of corporate governance mechanisms on disclosure of corporate social responsibility on company websites for companies engaged in the finance sector in Indonesia. This research refers to research conducted by Matuszak and Różańska (2019). Based on signal theory, the influence of corporate governance mechanisms on disclosure of corporate social responsibility has a positive influence. The research was conducted by taking a sample of 85 companies engaged in the finance sector. This research was taken using purposive sampling method and tested using multiple regression analysis method, classical assumption test and fit and goodness test. The results of the study show that company size has a positive effect on disclosure of corporate social responsibility. Meanwhile, profitability, leverage, and public ownership structure have absolutely no effect on the disclosure of corporate social responsibility.